Do India’s activities in Africa liberate and strengthen Africa’s position in the Euro-African relation? - Schrijen, Ton; Pennink, Bartjan (Archives of Business Research, 2017)
Abstract This research will analyze the economic relationship between India and Africa by analyzing trade, investments, aid and trade agreements. Moreover, this study will investigate whether there is substitution effect for the economic relationship between Europe and Africa and compare the results to China. The engagements of India appear to be stronger in resource rich countries and prove no substitution effect for the relationship of Europe and Africa. Moreover, India is also behind China in terms of trade. However, while India’s engagement might be smaller than China’s and Europe’s engagement, it might be more beneficial to Africa as the exports provide Africa with a trade surplus, whereas China and Europe do not. Therefore, the trade between India and Africa is a positive development for Africa, especially as Africa manages to reinvest this surplus into the development of its own economy.